PENDUGAAN EMISI KARBONDIOKSIDA (CO2) PERMUKAAN TANAH DI HUTAN LARANGAN ADAT KENEGERIAN RUMBIO KECAMATAN KAMPAR KABUPATEN KAMPAR - Adi Saputra; Rudianda Sulaeman; Defri Yoza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The forestry sector in Indonesia is one of the main sources of greenhouse gases (GHG), given the extensive forests owned Indonesia is one of the largest in the world, along with the high rate of deforestation, forest degradation and degraded land. Forests as one ecosystem dominated by trees vegetation, has the ability to absorb carbondioxide (CO2) from the air and carbon stock in the form of biomass. Indigenous forest Prohibition in the villages Rumbio, Pulau Sarak, Padang Mutung and Koto Tibun is one form of local wisdom that have been implemented long ago by societyof  indigenous forest prohibition Kenegerian Rumbio with the aim of maintaining the existence of the forest. This study aimed to quantify the potential emissions of carbondioxide (CO2) in the area of indigenous forests prohibition Kenegerian Rumbio. Potential emissions of CO2 in the soil surface at indigenous forests prohibition Kenegerian Rumbiois 1824.15 t/ha/yr. Overall potential emissionsof CO2in the soil surfaceat indigenous forests prohibition Kenegerian Rumbio is 966,799.5 t/y. Sparse vegetation density of CO2 emissions from the soil surface was higher (125.48 t/ha/yr) then moderate vegetation (84.50 t/ha/yr) and dense vegetation (61.10 t/ha/yr). Differences related CO2 emissions released by the micro-climate conditions such as air temperature and soil temperature, as well as the rate of CO2 emissions from the soil surface in each type of vegetation density.Keywords:  Emissions, Carbondioxside (CO2), Rumbio, Kampar